RECONSTRUCTION OF POSSIBLE POSITIONS OF FIRING (Journal of Forensic Medicine & Toxicology, 2024)
Reconstruction of crime scene and verification of possibilities of positions in shooting cases is important to enable court in arriving at a definite conclusion. Both ballistics expert and doctors are required to answer questions in the court of law regarding such matters. Trigonometry and geometry are used in shooting incident analysis. Singh and Mazumdar 5 established four geometrical relations for estimation of range of firing while the shooter is at different ground levels and firing upward and down ward. In shooting cases where the victim is standing erect these relations can be applied. In this paper a relation is established to estimate the range of firing which can be applied in shooting cases where the victim or deceased is lying on the ground. These relations involve parameters like muzzle height, range of firing, ground level slope, height of entry and exit holes and length of hole track. The last three parameters can be known from the post mortem and use in these relations. Thus, when any two of the first three parameters are known the remaining one can be estimated by using these relations. By using this technique possibilities of various positions of firings can be verified. In this paper, as examples, different possibilities of positions of firings for two gunshot holes (one each for elevated and depressed line of firing) are analysed with the hole data from post mortem report.
Keywords: Reconstruction; mortem